Spiritual Motivation and Religious Performance: a Case Study on Employees of Sharia Business Unit of Regional Development Bank in South Sumatera - Muhammad Ichsan Hadjri; Badia Perizade; Zunaidah Zunaidah; Yos Karimudin (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of spiritual motivation which consists of aqidah motivation, worship motivation, and muamalah motivation, either partially or simultaneously on the religious performance of employees of sharia business unit at the Regional Development Bank in South Sumatra. The population in this study were employees of the Sharia Business Unit at the Regional Development Bank in South Sumatra. The sampling method used was the determination of hotel samples by proportional stratified random sampling. Respondents in the study were 79 employees of the Sharia Business Unit at the Regional Development Bank in South Sumatra. The instrument for measuring the variables in this study was a questionnaire distributed to respondents. The questionnaire was measured using a Likert scale of 1-5. The data analysis technique used is multiple linear analysis. The results of the study concluded that the aqidah motivation, worship motivation, and muamalah motivation partially had a positive and significant effect on the religious performance on religious performance on employees of the Sharia Business Unit at the Regional Development Bank in South Sumatra. The results also show that the aqidah motivation, worship motivation, and muamalah motivation simultaneously had a positive and significant effect on the religious performance on employees of the Sharia Business Unit at the Regional Development Bank in South Sumatra. This research is limited in the number of respondents and the variables studied. This study is expected to be a reference for other researchers who want to the religious performance on employees of sharia banks. Contribution: This research studies deeply about the concept of spiritual motivation and religious performance. The proposition of the variables in this study has never been studied before, either conceptually or in the unit of analysis, namely sharia business unit of Regional Development Bank in South Sumatra and has become a novelty of this research